Dose reconstruction in workers exposed to two major pyrethroid pesticides and determination of biological reference values using a toxicokinetic model. (November 2018) - Côté, Jonathan; Bouchard, Michèle
Abstract A toxicokinetic model has been optimized to describe the time profiles of common biomarkers of exposure to permethrin and cypermethrin:trans -3-(2, 2-dichlorovinyl)-2, 2-dimethylcyclopropane-1-carboxylic acids (trans -DCCA) and 3-phenoxybenzoic acid (3-PBA). The model then served to reproduce urinary time courses in exposed agricultural workers and predict corresponding absorbed doses. It allowed for the prediction of the main routes of exposure in workers during the study period. Modeling showed that simulating exposure mostly by the oral route, during the 3-day biomonitoring period, provided best-fits to the urinary time courses of most workers. This is compatible with an inadvertent oral exposure during work. According to best-fit scenarios, absorbed doses in workers reconstructed with the model reached a maximum of 2.4 µg/kg bw/day and were below the absorbed dose limits associated with an exposure to the reference dose values established by the U.S. Environmental Protection Agency (0.06 and 0.25 mg/kg bw/day for cypermethrin and permethrin, respectively) and the Acceptable Operator Exposure Level set by the European Commission (0.06 mg/kg bw/day for cypermethrin). Modeling was further used to derive biological reference values for cypermethrin and permethrin exposure. Respective values of 7 and 29 nmol/kg bw/day oftrans -DCCA, and 3 and 13 nmol/kg bw/day of 3-PBA were obtained. None of the workers presented values above these biological reference values.